Interest rate surprises: A tale of two shocks - Ricardo Nunes; Ali Ozdagli; Jenny Tang (Federal Reserve Bank of Boston, 2022)
Interest rate surprises around FOMC announcements reveal both the surprise in the monetary policy stance (the pure policy shock) and interest rate movements driven by exogenous information about the economy from the central bank (the information shock). In order to disentangle the effects of these two shocks, we use interest rate changes on days of macroeconomic data releases. On these release dates, there are no pure policy shocks, which allows us to identify the impact of information shocks and thereby distill pure policy shocks from interest rate surprises around FOMC announcements. Our results show that there is a prominent central bank information component in the widely used high-frequency policy rate surprise measure that needs to be parsed out. When we remove this central bank information component, the estimated effects of monetary policy shocks are more pronounced relative to those estimated using the entire policy rate surprise.
Keywords: C36; D83; E52; E58; 330; monetary policy; central bank information; high-frequency identification; proxy structuralVAR; external instruments